Empowering Cloud of Things with Edge Computing: A Comparative Analysis - Mohsin, Sajjad Muhammad; Aslam, Sheraz; Akber, Syed Muhammad Abrar; Iqbal, Arshad; Waheed, Abdul; Ikram, Amra (My University, 2020)
Number of networks and their sizes in terms of connected devices are increasing very rapidly. These devices are producing massive amount of raw data for different progressive purposes that need to be processed and stored somewhere. Local data storage and complete processing of massive data will not be possible by resource constrained Internet of Things (IoT) enabling devices anymore in the future. Therefore, there is a need of data storage and processing capabilities to meet the desired goals of applications. Cloud computing and edge computing are the possible solution to circumvent limited data storage and computation issues of IoT devices. This paper presents a comparative study of popular architectures in which IoT devices are integrated with cloud. For this purpose, various IoT and Cloud of Things (CoT) architectures have been studied. Strengths and weaknesses of the studied IoT and CoT architectures are comprehensively analyzed on the basis of five comparison parameters namely; resource based segregation of IoT enabling devices, range based segregation of the communication network, segregation of security solutions, cloud connectivity, and edge computing services.
Keywords: Cloud Computing; Cloud of Things; Device Resources; Edge Computing; Internet of Things; Security